A Regulatory miRNA–mRNA Network Is Associated with Tissue Repair Induced by Mesenchymal Stromal Cells in Acute Kidney Injury - de Almeida, Danilo Candido; Bassi, Ênio Jose; Azevedo, Hatylas; Anderson, Letícia; Origassa, Clarice Silvia Taemi; Cenedeze, Marcos Antônio; Andrade-Oliveira, Vinicius de; Felizardo, Raphael José Ferreira; Silva, Reinaldo Correia da; Hiyane, Meire Ioshie; Semedo, Patricia; Reis, Marlene Antônia dos; et al. (Frontiers in Immunology, 2017)
Mesenchymal stromal cells (MSCs) orchestrate tissue repair by releasing cell-derived microvesicles (MVs), that presumably by small RNA species, modulate global gene expression. The knowledge of miRNA/mRNA signatures linked to a reparative status may elucidate some of the molecular events associated with MSC protection. Here, we used a model of cisplatin-induced kidney injury (AKI) to assess how MSCs or MVs could restore tissue function. MSCs and MVs presented similar protective effects, which were evidenced in vivo and in vitro by modulating apoptosis, inflammation, oxidative stress and a set of pro-survival molecules. In addition, we observed that miRNAs (i.e., miR-880, miR-141, miR-377 and miR-21) were modulated, showing active participation on regenerative process. Subsequently, we identified that MSC regulates a particular miRNA subset whose mRNA targets are associated with Wnt/TGF-β, fibrosis and epithelial-mesenchymal transition signaling pathways. Our results suggest that MSCs release MVs that transcriptionally reprogram injured cells, modulating a specific miRNA-mRNA network.